What should be the goal of our environmental efforts? - Vladimir Arutyunov (Global Journal of Ecology - Peertechz Publications, 2022)
The world's population has already reached almost 8 billion people and continues to grow rapidly. Environmental and climatic changes caused by human activity are continuously progressing; therefore, their impact on the further development of civilization has become one of the most acute and widely discussed problems.